2016
DOI: 10.2503/hortj.mi-103
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Soluble Carbohydrates and Their Subcellular Concentrations in Petals during Flower Opening in <i>Eustoma grandiflorum</i>

Abstract: Petal growth associated with flower opening is due to cell expansion. To elucidate the role of soluble carbohydrates in expansion of petal cells in Eustoma grandiflorum, its soluble carbohydrates were identified, and changes in their subcellular concentrations during flower opening were investigated. In addition to glucose, fructose, sucrose, and myo-inositol, D-bornesitol was identified using 1 H-NMR. D-Bornesitol was the major soluble carbohydrate in leaves and stems. Given that cyclitols are known to be the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…Numerous reports showed that exogenous sugar is indispensable for sustaining lisianthus flower life, both as a respiration substrate [16] and as an osmolyte that promotes water influx into expanding petals, thus enhancing bud opening [35]. The number of open buds on stems held in sucrose solutions was always higher than those in solutions without sugar [15,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous reports showed that exogenous sugar is indispensable for sustaining lisianthus flower life, both as a respiration substrate [16] and as an osmolyte that promotes water influx into expanding petals, thus enhancing bud opening [35]. The number of open buds on stems held in sucrose solutions was always higher than those in solutions without sugar [15,36].…”
Section: Discussionmentioning
confidence: 99%
“…As sucrose is a transportable form of carbohydrates within lisianthus stems [35], it has mainly been used to extend the vase life, and generally it is more effective than glucose or fructose [10]. The reported sucrose concentrations in holding solutions for lisianthus range between 2% [4,10,17] and 6% [14], while 5% has been used for 18 h conditioning [3].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, soluble carbohydrates depending on the degradation of polysaccharides can act as osmotically active compounds which could lower the osmotic water potential and facilitate water influx in order to allow cell expansion [12]. The concentration of soluble carbohydrates in the petals will increase in the flower opening process of plants such as carnation [13], rose [14], chrysanthemum [15], Tweedia caerulea [16], and lisianthus [17].…”
Section: Introductionmentioning
confidence: 99%
“…Soluble carbohydrates depending on the degradation of polysaccharides can act as osmotically active compounds which could lower the osmotic water potential and facilitate water influx in order to allow cell expansion [12]. The concentration of soluble carbohydrates in the petals will increase in the flower opening process such as carnation [13], rose [14], chrysanthemum [15], Tweedia caerulea [16], and lisianthus [17].…”
Section: Introductionmentioning
confidence: 99%